Cell-specific paracrine actions of IL-6 family cytokines from bone, marrow and muscle that control bone formation and resorption. (October 2016) - Sims, Natalie A.
Abstract: Bone renews itself and changes shape throughout life to account for the changing needs of the body; this requires co-ordinated activities of bone resorbing cells (osteoclasts), bone forming cells (osteoblasts) and bone's internal cellular network (osteocytes). This review focuses on paracrine signaling by the IL-6 family of cytokines between bone cells, bone marrow, and skeletal muscle in normal physiology and in pathological states where their levels may be locally or systemically elevated. These functions include the support of osteoclast formation by osteoblast lineage cells in response to interleukin 6 (IL-6), interleukin 11 (IL-11), oncostatin M (OSM) and cardiotrophin 1 (CT-1). In addition it will discuss how bone-resorbing osteoclasts promote osteoblast activity by secreting CT-1, which acts as a "coupling factor" on osteocytes, osteoblasts, and their precursors to promote bone formation. OSM, produced by osteoblast lineage cells and macrophages, stimulates bone formation via osteocytes. IL-6 family cytokines also mediate actions of other bone formation stimuli like parathyroid hormone (PTH) and mechanical loading. CT-1, OSM and LIF suppress marrow adipogenesis by shifting commitment of pluripotent precursors towards osteoblast differentiation. Ciliary neurotrophic factor (CNTF) is released as a myokine from skeletal muscle and suppresses osteoblast differentiation and bone formation on the periosteum (outer bone surface in apposition to muscle). Finally, IL-6 acts directly on marrow-derived osteoclasts to stimulate release of "osteotransmitters" that act through the cortical osteocyte network to stimulate bone formation on the periosteum. Each will be discussed as illustrations of how the extended family of IL-6 cytokines acts within the skeleton in physiology and may be altered in pathological conditions or by targeted therapies.